Benthic Conservation Features and Species Associated With Subsea Pipelines: Considerations for Decommissioning - Rouse, Sally; Lacey, Nichola C.; Hayes, Peter; Wilding, Thomas A. (Frontiers in Marine Science, 2019)
Oil and gas pipelines that lie exposed on the seabed can function as “artificial reefs”, providing habitat for fish and benthic species, including some that are listed under conservation designations. As the offshore hydrocarbon industry matures, operators and national governments must decide whether decommissioned pipelines should be left in situ or removed for onshore disposal. In most jurisdictions, there is a requirement to evaluate the environmental consequences of different pipeline decommissioning options in a comparative assessment. To do this effectively requires an understanding of the associations between pipelines and fauna. Pipeline operators routinely collect video footage for inspection and maintenance purposes using remotely operated vehicles (ROV). This footage has the potential to provide insight into interactions between the marine environment and offshore pipelines. This study uses inspection footage from eight pipelines to quantify the presence and abundance of species and features listed under a number of EU and UK conservation designations; 12 such features and species were observed on the pipelines or neighboring sediments. The soft coral Alcyonium digtatum was present in the highest densities on pipelines located on mud, while Sabellaria sp. and Echinus esculentus were more common on pipelines in sand. Gadoids, anemones and hermit crabs were also frequently observed around pipelines. The study also suggests that faunal identification from ROV footage depended on image resolution, ROV speed and altitude, and lighting, and taxa <50 mm in size could not be reliably classified. The results suggest that removal of pipelines will remove established colonies of epibenthic species, some of which have conservation value. The ecological significance of this loss, however, must be weighed against the broader considerations during pipeline decommissioning including cost, technical feasibility and impacts to other marine users.